Critical Roles for Bradykinin and Prostanoids in Acute Inflammatory Reactions: A Search Using Experimental Animal Models - Ueno, A.; Oh-ishi, S. (Current Drug Targets - Inflammation & Allergy, 2002)
Searches for chemical mediators of inflammation underlying classical signs of inflammation i.e. heat, redness, swelling, and pain have been performed and various experimental models for evaluation of new agents to manage these inflammatory signs have been developed extensively during the last century. Now, at the beginning of the 21st-century, after great progress in gene technology, the necessity of in vivo animal study is being reconsiderered. Therefore, this review introduces and describes findings obtained by the use of various experimental animal models. We have compared the inflammatory characteristics among species using reported animal models such as dye exudation in the skin, paw edema, pleurisy, and writhing reaction, then we have precisely examined mediators involved in these inflammatory reactions. In the process of plasma exudation and pain perception in the earlier phases of acute inflammation, involvement of the kallikrein-kinin system and prostanoids was demonstrated. Precisely, bradykinin, and PGI2 among the prostanoids, are major mediators for exudation and pain perception of the initial acute phase of inflammation, both mediators collaborate to enhance these effects. PGE2, perhaps produced by cyclooxygenase-2, was involved in induction of plasma exudation and pain perception in a later phase than the timing of involvement of PGI2. Precise roles of various prostanoids will hopefully be clarified by the research projects in progress.
Keywords: paw edema